Bidirectional Communication System on Power Line Integrated on Electronic Board for Driving of LED and HID Lamps. (14th February 2012) - Visconti, P.; D'Amico, S.; Baschirotto, A.; Romanello, D.; Costantini, P.; Ventura, V.; Cavalera, G.
Abstract : We present the bidirectional power line communication system developed in parallel to an electronic board for driving and control of HID (high-intensity discharge) and LED (light-emitting diode) lamps. The communication system, developed to be applied in the sector of public illumination, is been designed to combine high efficiency and reliability with low production costs; it consists indeed of discrete cheap components. The communication system described in this paper implements the technique of transporting digital information over existing power lines, avoiding the issue of installing new cables. Digitized signals can use power line cables through the amplitude voltage and current modulation. The solution proposed is more advantageous compared to communication techniques currently on the market which are essentially two types, power line carrier (modem for high-voltage lines) or radio (zig-Bee transceiver).